2018
DOI: 10.1016/j.aquatox.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

An AOP-based alternative testing strategy to predict the impact of thyroid hormone disruption on swim bladder inflation in zebrafish

Abstract: The adverse outcome pathway (AOP) framework can be used to help support the development of alternative testing strategies aimed at predicting adverse outcomes caused by triggering specific toxicity pathways. In this paper, we present a case-study demonstrating the selection of alternative in chemico assays targeting the molecular initiating events of established AOPs, and evaluate use of the resulting data to predict higher level biological endpoints. Based on two AOPs linking inhibition of the deiodinase (DIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 115 publications
(142 reference statements)
0
53
0
Order By: Relevance
“…However, TH signaling may be necessary for the proper developmental remodeling process in zebrafish. Originally, the role of THs in zebrafish development was studied using goitrogen treatments [44][45][46], which biologically block TH synthesis in thyrocytes and induce the hypothyroid state. The conclusions of the LTJT studies with goitrogen treatments can be confusing as the chemicals used in these studies also generate risks due to toxicity associated with non-TH-related side effects [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, TH signaling may be necessary for the proper developmental remodeling process in zebrafish. Originally, the role of THs in zebrafish development was studied using goitrogen treatments [44][45][46], which biologically block TH synthesis in thyrocytes and induce the hypothyroid state. The conclusions of the LTJT studies with goitrogen treatments can be confusing as the chemicals used in these studies also generate risks due to toxicity associated with non-TH-related side effects [47].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, when observed bioactivities/targets can be linked to known pathways/processes, for example using AOPs, insights as to susceptible species and sensitive endpoints can be gained. As a simple illustration of this, Stinckens et al (2018) reported that PFOA caused significant inhibition of the activity of deiodinases involved in thyroid hormone synthesis using in vitro assays with liver tissue from pigs.…”
Section: Accepted Articlementioning
confidence: 99%
“…The AOP network used in this case example links TH disruption to impaired swim bladder inflation in fish and is mainly based on experimental evidence from studies on zebrafish and fathead minnow including chemical exposures, knockdowns, knockouts and rescue experiments [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . The swim bladder is an internal gas-filled organ found in many bony fish species and typically consists of two gas-filled chambers.…”
Section: Brief Description Of the Aop Networkmentioning
confidence: 99%
“…Specifically, a positive result in the in vitro Tpo and/or the Dio inhibition assay could trigger fish in vivo testing to confirm the occurrence of downstream events along the AOP network including altered TH levels, impaired swim bladder inflation, and altered swimming performance (see sections 3.2 and 3.3). An initial validation case study showed that adverse swim bladder effects could be predicted along the AOP network based on in vitro Dio inhibition data 22 . The further development of such predictive approaches, including expanding the quantitative understanding of the relationships depicted in the AOPs where possible 42 , would significantly reduce the need for in vivo testing in the future.…”
Section: In Vitro Assays For Thyroid Activity Screeningmentioning
confidence: 99%